2008
DOI: 10.1121/1.2949519
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound attenuation estimation using backscattered echoes from multiple sources

Abstract: The objective of this study was to devise an algorithm that can accurately estimate the attenuation along the propagation path ͑i.e., the total attenuation͒ from backscattered echoes. It was shown that the downshift in the center frequency of the backscattered ultrasound echoes compared to echoes obtained in a water bath was calculated to have the form ⌬f = mf o + b after normalizing with respect to the source bandwidth where m depends on the correlation length, b depends on the total attenuation, and f o is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 43 publications
0
27
1
Order By: Relevance
“…F ( ω,a eff ) has been shown to be approximately proportional to exp(− Af n ) for most scattering models where A ~ (2 πa eff / c ) n with a eff being the effective radius of the tissue microstructure, c being the speed of sound in the tissue, and n ≅ 2 [17]. Therefore, as was shown in [16], [17], truef~o and trueσ~ω2 are given by rightleftf~ofo4zTαoσ~ω2σ~ω2Anforightleftσ~ω2σω21+Anσω2. Hence, truef~o depends on both the attenuation along the propagation path and the frequency dependence of the backscatter, whereas trueσ~ω2 only depends on the scattering.…”
Section: Derivation Of Ss Algorithmmentioning
confidence: 93%
See 3 more Smart Citations
“…F ( ω,a eff ) has been shown to be approximately proportional to exp(− Af n ) for most scattering models where A ~ (2 πa eff / c ) n with a eff being the effective radius of the tissue microstructure, c being the speed of sound in the tissue, and n ≅ 2 [17]. Therefore, as was shown in [16], [17], truef~o and trueσ~ω2 are given by rightleftf~ofo4zTαoσ~ω2σ~ω2Anforightleftσ~ω2σω21+Anσω2. Hence, truef~o depends on both the attenuation along the propagation path and the frequency dependence of the backscatter, whereas trueσ~ω2 only depends on the scattering.…”
Section: Derivation Of Ss Algorithmmentioning
confidence: 93%
“…Previously, we derived an algorithm for estimating the slope of the total attenuation along the propagation path assuming a linear dependence on frequency and demonstrated that the algorithm yielded accurate results in computer simulations [16], [17]. One difficulty in implementing the algorithm, however, is that it requires scanning the same tissue region with multiple single-element spherically focused sources.…”
Section: Derivation Of Ss Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, this approach requires MB destruction, which is related to increased cell death. An estimation of tissue attenuation can be determined from backscattered high frequency image data of a tissue region, as presented by Bigelow [9] and Labyed [10]. In this setup, that algorithm allows to determine the total attenuation of overlaying tissue layers, when analyzing the phantom region just above the MB channel, as displayed in Fig.…”
Section: Tissue Transfer Function Estimationmentioning
confidence: 99%